A Study on Factors for Religious Faith of Muslim Youth in China - Ma, Kuaichong (Transactions on Economics, Business and Management Research, 2024)
This study investigates the factors influencing the religious faith of Hui Muslim youth in China, focusing on internal and external elements. The study used a mixed-methods approach, integrating quantitative surveys and qualitative interviews done in multiple mosques in Shanghai. Examined include external elements such as social integration, governmental policies, and educational environments, as well as internal factors such as personal beliefs, family influence, and community support. The results show that among young Hui Muslims, self-interest and family support are strongly associated with stronger religious faith. Moreover, the employment of digital media and virtual communities has emerged as a crucial component in fostering religious engagement, offering new avenues for religious education and community building. This study provides insights for policymakers, educators, and religious leaders to better support the religious and cultural needs of Hui Muslim youth in China.